Efeito do tratamento alcalino e a plasma das fibras de sisal nas propriedades de tração de biocompósitos a base de fécula de mandioca - Barbosa, Larissa Moreira (Universidade Federal Rural do Semi-Árido, 2021)
The growing environmental appeal is triggering more and more studies to replace petrochemical products with biodegradable products from renewable sources, in order to seek the sustainable development of the planet. With this, the use of natural plastic materials, such as starch and chitosan, has been encouraged and improved to obtain a better performance. One way to increase the performance of natural plastics is to use natural fibers in polymeric composite materials to modify their mechanical properties. In this work, a biocomposite from cassava starch and sisal fiber was developed, where the mechanical properties of limit of tensile strength, elongation and modulus of elasticity were analyzed. First, a study of the drying conditions of the material was carried out, analyzing the interference of the drying temperature modification in relation to the properties. An experimental design was also carried out, DIC (Fully Randomized Design), varying the starch and fiber content to choose the best composition according to the mechanical properties. Finally, the sisal fiber was chemically treated, with sodium hydroxide in a concentration of 5% and physically, with plasma type DBS (barrier dielectric discharge) at atmospheric pressure and using atmospheric gases. The biocomposites made up of cassava starch and sisal fiber were produced and then mechanical and morphological tests were carried out to observe the change in the mechanical properties and the interaction of the fiber with the matrix. The results showed that only the modulus of elasticity has a significant change in relation to the temperature variation. Within the analysis of the experimental design it was observed that the proportion 85% of cassava starch, 5% of sisal fiber and 10% of glycerol obtained better properties. The treatment of the fiber with plasma was the most adequate, due to the improvements in its mechanical properties; on the other hand, the composite with fiber treated with NaOH had no relevant changes in its properties in comparison with the natural fiber, leaving the material more fragile
Keywords: Tratamento com NaOH; Tratamento com plasma; Condições de secagem; Propriedades mecânicas; NaOH treatment; Plasma treatment; Drying conditions; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA